The Convergence of Economic Growth between District/Cities in Papua Province - Theresia Oktavia; Teguh Hadi Priyono; Duwi Yunitasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Differences in economic growth, geographical conditions, and potential between regions cause development inequality. Therefore, there is a need for inter-regional convergence. The convergence will explain the equality of economic growth between regions. Papua Province has 29 regencies/cities with different economic characteristics and inequality. The purpose of this study was to determine the convergence in Papua Province based on the concept of convergent sigma and beta. This research was conducted using panel data regression analysis techniques. The research method used is sigma convergence, absolute beta convergence, and conditional beta convergence. The results of this study are the existence of sigma convergence, absolute beta convergence, and conditional beta convergence between districts/cities in Papua Province in 2010-2020. In addition, there is a positive and significant correlation between education, electricity, and economic growth, but there is no significant relationship between roads, vehicles, and economic growth.